Legal Education and its Contemporary Challenges in Sub-Saharan Africa - Kankindi, Antoinette; Chimbwanda, Victor (Strathmore Law Journal, 2021)
There is an increasing criticism against law schools. To some, the system does not sufficiently prepare students for the market or to meet society’s needs. Others argue that technology and current trends should inspire new business models in the legal profession. Legal education is also being accused of emphasising theoretical content rather than skills necessary for practice, with the character of African jurisprudence struggling for recognition in the contemporary curriculum. Moreover, a fragmented society under pressure from global shifting values also faces perennial legal challenges relating to issues of justice and other ethical problems trained lawyers may face. Therefore, the role of legal education ought to be re-examined to prioritise the common good without threatening individual interests, which is what the rule of law aims at achieving. This paper investigates the problem from the perspective of unity of knowledge to address the traditional theory-andpractice divide in legal education and argues that the idea of unity of knowledge provides the basis for a correct interdisciplinary approach to solving the problem, relying on systems of legal training as they have developed in some parts of Africa especially Kenya, Nigeria and South Africa. Considering such illustrations, this framework is also likely to enable a rational articulation of theory and practice in legal training that can create more space for African views of law as reflected in the current efforts to decolonise legal education in South Africa.